Perception Of Chess Athletes Towards The National Sports Grand Design - Medina Warda Aulia; Lina Miftahul Jannah (Green Publisher Indonesia, 2024)
Athletes are the main actors in a sports competency. In connection with sports, in 2021 President of the Republic of Indonesia Joko Widodo has signed Presidential Regulation of the Republic of Indonesia (Perpres) Number 86 of 2021 concerning the Grand Design of National Sports or DBON which has the aim of increasing sports culture in society; increasing the capacity, synergy and productivity of national achievement sports; and advancing the sports-based national economy. The purpose of this study was to determine the perceptions of chess athletes towards DBON. The method used is a description method with a qualitative approach. The data collection techniques used are interviews and literature studies. The data analysis carried out is by triangulation analysis. The results showed that chess athletes' perceptions of DBON varied. However, the majority of athletes are of the view that the birth of Presidential Regulation Number 86 of 2021 concerning the Grand Design of National Sports provides maximum opportunities and opportunities for athletes to get better support and facilities, including training, equipment, and opportunities to participate in various higher competencies.